The Concept of "New Uzbekistan-Enlightened Society" As a Factor of Spiritual Upgrade (Zien Journal of Social Sciences and Humanities, 2023)
This article presents a lot of scientific information about the concept of "new Uzbekistanenlightened society" as a factor of spiritual growth.